2015
DOI: 10.1159/000375170
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation in Patients with Chronic Respiratory Disease Other than Chronic Obstructive Pulmonary Disease: Exercise and Physical Activity Interventions in Cystic Fibrosis and Non-Cystic Fibrosis Bronchiectasis

Abstract: A relevant proportion of children and adults with cystic fibrosis (CF) have a marked decrease in exercise tolerance, which can be partly related to impaired muscle function and decreased physical activity levels in daily life, in addition to lung disease. Preliminary findings suggest that patients with non-CF bronchiectasis face the same problems. These patients might be excellent candidates for exercise and physical activity interventions. This review elaborates on the rationale for exercise training and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 95 publications
2
44
1
6
Order By: Relevance
“…The physical training provided during PR seems to be the main reason for the improvements in the 6MWD, especially since marginally reduced lung function values were only slightly improved at T1 and thus cannot be responsible for these results. The importance of muscular weakness in sarcoidosis patients has been frequently described in the literature [6, 8, 15-17, 40]. Our results document a significant improvement in functional exercise capacity immediately following the 3-week PR programme, especially in the previously very impaired patients.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The physical training provided during PR seems to be the main reason for the improvements in the 6MWD, especially since marginally reduced lung function values were only slightly improved at T1 and thus cannot be responsible for these results. The importance of muscular weakness in sarcoidosis patients has been frequently described in the literature [6, 8, 15-17, 40]. Our results document a significant improvement in functional exercise capacity immediately following the 3-week PR programme, especially in the previously very impaired patients.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, our results suggest that a 3-week inpatient PR programme shows benefits comparable to a 12- or 13-week outpatient training programme regarding functional exercise capacity. This benefit of PR is particularly important, as several studies [8, 15, 21] have shown that exercise intolerance is linked to reduced QoL, dyspnoea, and fatigue, thus frequently creating a persistent vicious circle, as has also been described for other pulmonary diseases [5, 6]. PR can potentially break this circle by increasing exercise capacity and thus enhance physical activity levels in daily life [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These disturbances may affect the lungs, as well as respiratory mechanics, where the presence of both conditions can contribute to dyspnoea and may ultimately lead to respiratory failure. Furthermore, chronic P. aeruginosa infection and high IgG levels were shown to be associated with a decline in exercise capacity in adolescent patients with CF [5], and a decreased exercise capacity is found in a relevant proportion of patients with CF [6]. Despite the link between P. aeruginosa infection and respiratory disturbances, respiratory mechanics are rarely investigated in CF patients.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond disease-related factors, a lack of PA might contribute to peripheral muscle abnormalities [5,8]. Physical exercise training has potential therapeutic effects on exercise capacity, pulmonary function, peripheral muscle dysfunction and health-related quality of life (HRQoL) [5,9,10]. Despite these benefits, most, but not all, patients with CF display low levels of PA and exercise training [11].…”
Section: Introductionmentioning
confidence: 99%